IMPROVING HISTORY LEARNING OUTCOMES THROUGH THE DISCOVERY LEARNING MODEL FOR CLASS XII STUDENTS AT SMAN 2 MEDAN - Lamsar Latinus Sihombing; Muhammad Adika Nugraha; Sitti Aisyah (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to investigate the effectiveness of the Discovery Learning learning model in improving student learning outcomes in history subjects at the senior high school level. The research was conducted at SMA Negeri 2 Medan, with the research subjects being class XII students. The experimental research method was used with a pre-test and post-test control group design. The experimental group applied the Discovery Learning learning model, while the control group applied conventional learning. Data was collected through pre- and post-tests as well as classroom observations. Data analysis was carried out using an independent t-test. The research results showed that students who participated in learning using the Discovery Learning model produced significant improvements in their learning outcomes compared to the control group. This research concludes that the application of the Discovery Learning model is effective in improving the history learning outcomes of class XII students at SMA Negeri 2 Medan. Implications and suggestions for future research are also discussed. Thus, the conclusion of this research is that the Discovery Learning learning model has the potential to improve student learning outcomes and make a significant contribution to efforts to improve the quality of education at SMA Negeri 2 Medan and perhaps also in other educational institutions.